2014
DOI: 10.1182/blood-2013-10-532523
|View full text |Cite
|
Sign up to set email alerts
|

GPR84 sustains aberrant β-catenin signaling in leukemic stem cells for maintenance of MLL leukemogenesis

Abstract: Key Points• GPR84 simultaneously augments b-catenin signaling and an oncogenic transcription program essential for establishment of MLL.• Our study demonstrates a strong dependence of hematopoietic stem cell-derived MLL leukemic cells on GPR84 for disease maintenance in vivo.b-catenin is required for establishment of leukemic stem cells (LSCs) in acute myeloid leukemia (AML). Targeted inhibition of b-catenin signaling has been hampered by the lack of pathway components amenable to pharmacologic manipulation. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…The Wnt/β-catenin was active in human LSCs and in HSCs while β-catenin was unnecessary for the selfrenew of adult HSCs (43)(44)(45). Meanwhile, pharmacological inhibition of β-catenin impaired LSC function and significantly reduced the growth of human MLL leukemic cells (46,47). Therefore, all these transcription factors might be considered to be potential targets for selectively ablating LSCs.…”
Section: The Transcription Factors Of Lscs In Amlmentioning
confidence: 99%
“…The Wnt/β-catenin was active in human LSCs and in HSCs while β-catenin was unnecessary for the selfrenew of adult HSCs (43)(44)(45). Meanwhile, pharmacological inhibition of β-catenin impaired LSC function and significantly reduced the growth of human MLL leukemic cells (46,47). Therefore, all these transcription factors might be considered to be potential targets for selectively ablating LSCs.…”
Section: The Transcription Factors Of Lscs In Amlmentioning
confidence: 99%
“…Like normal tissues, tumour tissues are composed of a variety of heterogeneous tumour cells and originate from corresponding stem cells. CSCs have been isolated from a variety of tumours, such as leukaemia, lung cancer and breast cancer . There are two recognized methods of separating BCSCs from breast cancer patients and cell lines: one is surface phenotypic marker screening, and the other is Hoechst 33 342 dye exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study reported that GPR84 is a proinflammatory receptor and may be a target to treat chronic, low‐grade inflammation related‐disorders (Suzuki et al, ). GPR84 is also known to modulate leukemogenesis and to possess a novel therapeutic potential against acute myeloid leukemia (Dietrich et al, ). Although GPR84 has been reported to mainly regulate immune responses in many cell types, the role of GPR84 in osteoclast differentiation has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%